Modeling pathways to non-suicidal self-injury: The roles of perfectionism, negative affect, rumination, and attention control - Tonta, Kate; Boyes, Mark; Howell, Jennifer; McEvoy, Peter; Johnson, Andrew; Hasking, Penelope (WILEY, 2022)
Objective: Using the Emotional Cascade Model as a theoretical framework, this study tested whether the relationship between perfectionism and non-suicidal self-injury (NSSI) operates through rumination and negative affect. Additionally, we tested whether the associations between perfectionism and both rumination and negative affect are moderated by attention control. Methods: Using a correlational cross-sectional design, adults aged 18–25 with (N = 197) and without (N = 271) a history of NSSI completed measures of perfectionism, rumination, negative affect, attention control, and NSSI. Results: Perfectionism was directly associated with increased odds of NSSI, and indirectly associated with odds of NSSI through rumination and negative affect. The relationship between perfectionism and rumination was moderated by attention focusing, such that the relationship was stronger for individuals who were higher in attention focusing. Conclusion: Integrating perfectionism and attention with existing models of NSSI may improve understanding of the factors contributing to NSSI and offers insights into future clinical directions.